(untitled) (Computer systems and information technologies, 2024)
The network infrastructure is the basis for the effective functioning of the modern digital economy. The success of the Ukrainian economy additionally depends on the compatibility of its network infrastructure with the network infrastructure of the EU. Therefore, it is relevant to analyze the state of the network infrastructure in the EU, compare it with the state in Ukraine, in order to determine the challenges that Ukraine will need to overcome in the convergence of the Ukrainian digital economy with the EU digital economy. The relevance of the work is justified by the fact that the introduction of advanced digital network technologies, coordinated with European ones, is one of the ways to increase the future competitiveness of the Ukrainian economy. The Digital Economy and Society Index (DESI) summarizes a number of indicators of the effectiveness of digital technologies in Europe and allows us to assess the state of the digital economy and society. This work is devoted to analyzing one of the DESI indicators, namely, digital infrastructure, both in the European Union (EU) and Ukraine. The analysis covers the defined DESI 2023 digital infrastructures, such as at least 100 Mbps fixed broadband take-up, at least 1 Gbps broadband take-up, fixed Very High Capacity Networks (VHCN) coverage, Fiber-to-the-Premises (FTTP) coverage, mobile broadband take-up, 5G coverage, and 5G spectrum. We have shown that Ukraine currently has a good offer of FTTP technology, which can become the basis for the convergence of the digital infrastructure of Ukraine and the EU. However, according to our analysis, Ukraine urgently needs to accelerate the implementation of the 5G network, especially the 5G spectrum technology, which will contribute to the modernization and recovery of the national economy. The results of the analysis will be useful for the convergence of the digital economy of Ukraine with the European digital economy.